Twenty Years of Epithelial-Mesenchymal Transition: A State of the Field from TEMTIA X - Savagner, Pierre; Brabletz, Thomas; Cheng, Chonghui; Gilles, Christine; Hong, Tian; Polette, Myriam; Sheng, Guojun; Stemmler, Marc P.; Thompson, Erik W. (Cells Tissues Organs, 2024)
This report summarizes the 10th biennial meeting of The Epithelial Mesenchymal Transition International Association (TEMTIA), that took place in Paris on November 7 10, 2022. It provides a short but comprehensive introduction to the presentations and discussions that took place during the 3- day meeting. Similarly to previous TEMTIA meetings, TEMTIA X reviewed the most recent aspects of the epithelialmesenchymal transition (EMT), a cellular process involved during distinct stages of development but also during wound healing and fibrosis to some degree. EMT has also been associated at various levels during tumor cell progression and metastasis. The meeting emphasized the intermediate stages of EMT (partial EMT or EM hybrid cells) involved in the malignant process and their potential physiological or pathological importance, taking advantage of advancements in molecular methods at the single-cell level. It also introduced novel descriptions of EMT occurrences during early embryogenesis. Sessions explored relationships between EMT and cell metabolism and how EMT can affect immune responses, particularly during tumor progression, providing new targets for cancer therapy. Finally, it introduced a new perception of EMT biological meaning based on an evolutionary perspective. The meeting integrated the TEMTIA general assembly, allowing general discussion about the future of the association and the site of the next meeting, now decided to take place in Seattle, USA, in November 2024. This report provides a comprehensive introduction to the presentations and discussions that took place during the 10th biennial meeting of TEMTIA, that occurred in Paris on November 7 10, 2022. It includes all the sessions and follows the chronological order during the 3-day meeting. A general purpose of the meeting was to explore the boundaries of the EMT process, including new concepts and developments, as illustrated by our leitmotiv for the meeting, inspired by the proximity of the Cluny Museum in Paris.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Cancer; Development; Epithelial-mesenchymal transition